NILAI-NILAI PENDIDIKAN ISLAM DALAM AL-QUR‘AN (Telaah Surah Al-Fatihah) - Ibrahim Hasan (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2017)
Abstrak: The background of this research is because it is still found that a number of Islamiceducation in Indonesia has not applied yet the values that exist in the source of the teachings ofIslam itself that is the Quran. So this study aims to analyze the values of Islamic education containedin the surah al-Fatihah and connect the values of Islamic education with Islamic education. The resultof this study is expected to add a new perspective in order to apply the values of Islamic educationcontained in the Quran.This research is a library research using a philosophical approach which seeks to see the values ofIslamic education contained in skrah al-Fati%ah. The sources of data used are books of tafs+r Quranas primary data sources and other supporting books relating to research objects as secondary datasources. Technique of collecting data using is method of documentation. The data collected is thenanalyzed by using tahlily method, comparison, and interpretation.The results of this study indicate that: 1) There are values of Islamic education in skrah al-Fat%ah,namely: First, the value of faith education includes faith in God through His grace, faith in Godthrough the unity of His deeds, faith in God through His name and Character (ar-Rahmn and ar-Rh+m), and faith in the last day (retaliation). Second, the value of worship education in a broadsense, that is every activity of goodness done with purpose because Allah Swt and surrender to Godin running worship or deed which cannot be finished. Third, the value of sharia education in a broadsense, is that religion with all the laws contained therein. Fourth, the educational value of the storyincludes the stories of the people who get the favors, the stories of the people who get wrath and thelost. 2) There is a very close relevance between the values of Islamic education with Islamic education,namely: First, the Value of Faith serves as the basis of Islamic education covering all components ofeducation, ranging from educational goals, educational curriculum, methods of education, educationevaluation and so on which should be based on faith, because faith is the foundation in doing variousgood deeds. Second, the value of worship education serves as an educational goal, because one of thegoals of Islamic education is to make man as servant of Allah who is assigned only to worship Him.Third, the value of sharia education is used as the educational objective and educational curriculumso that people will keep the commandments and regulations of religion (syar+‘ah) that Allah hasassigned to His servants. Fourth, the value of education is used as the method of education in whichthe method of education is used in the learning process supported by the material of moral teachingsso that the purpose of Islamic education is manifested, that is to create a plenary man (whole) bornand inner (insn al-kmil), as well as good morality act.